USING GROUP WORK INTERVENTIONS TO ADDRESS THE PSYCHOSOCIAL IMPACT OF EXPOSURE TO DOMESTIC VIOLENCE ON ADOLESCENTS - Maphosa, Ntandoyenkosi (Social Work/Maatskaplike Werk, 2022)
Given the high prevalence rate of domestic violence (DV) in South Africa, one in four adolescents reportedly comes from a home where they are exposed to DV. The effects of exposure to domestic violence on adolescents are adverse and lifelong; therefore, providing effective treatment is crucial. Group work has proven to be effective in some international studies, but South Africa has limited research on this question, particularly on the psychosocial impact of DV exposure and the necessary effective interventions. Through an ethnography qualitative approach, this study aims to expand the limited knowledge base. Participants were observed during a group work process for a period of 8 weeks, the objective being to determine their psychosocial functioning after exposure to domestic violence. Drawing from social learning theory, the findings of the study suggest that adolescents can benefit from group work interventions. The results showed that the group participants’ psychosocial functioning improved significantly after the intervention. Based on the findings, policy and practice recommendations for adolescents exposed to domestic violence are made.